2023
DOI: 10.1101/2023.02.27.530095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic features and genomic targets of human KRAB-Zinc Finger Proteins

Abstract: Krüppel-associated box (KRAB) domain-containing zinc finger proteins (KZFPs) are one of the largest groups of transcription factors encoded by tetrapods, with 378 members in human alone. KZFP genes are often grouped in clusters reflecting amplification by gene and segment duplication since the gene family first emerged more than 400 million years ago. Previous work has revealed that many KZFPs recognize transposable element (TE)-embedded sequences as genomic targets, and that KZFPs facilitate the co-option of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…Interestingly, we recovered a dominant, new peak on chromosome 4 that was associated with L1M3a RNA levels but to which we could not attribute a protein-coding mediator. The index SNV for this locus, rs6819237, resides within an intron of ZNF141 , which has been shown to bind L1PA elements (de Tribolet-Hardy et al 2023). Second, the eQTL scan using the nearby intergenic L1 profiles recapitulated the results of our initial scan for the HLA loci ( Supplementary Figure S7B, Supplementary Table S3F) .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we recovered a dominant, new peak on chromosome 4 that was associated with L1M3a RNA levels but to which we could not attribute a protein-coding mediator. The index SNV for this locus, rs6819237, resides within an intron of ZNF141 , which has been shown to bind L1PA elements (de Tribolet-Hardy et al 2023). Second, the eQTL scan using the nearby intergenic L1 profiles recapitulated the results of our initial scan for the HLA loci ( Supplementary Figure S7B, Supplementary Table S3F) .…”
Section: Resultsmentioning
confidence: 99%
“…HEK293T cells overexpressing HA-tagged constructs were generated as described in de Tribolet-Hardy et al, 2023 1 . In short, cDNAs for ZNF274 constructs were codon-optimized, synthesized using the GeneArt service from ThermoFisher and cloned into the doxycycline inducible expression vector pTRE-3HA.…”
Section: Methodsmentioning
confidence: 99%
“…Krüppel-associated box (KRAB) domain-containing zinc-finger family proteins (KZFP) are one of the largest groups of transcription factors in tetrapods (de Tribolet-Hardy et al, 2023). It has been reported that the expressed HERVs in tumors (such as LTR70, LTR25, LTR5B, and LTR5_Hs) are predominantly in the vicinity of TSSs of KZFP genes and some of these HERVs could act as enhancers modulating the expression of KZFP genes in LUAD cells (Ito et al, 2020).…”
Section: Lung Cancermentioning
confidence: 99%